EVALUATION OF BIOACTIVE COMPOUNDS, ANTIOXIDANT, AND ANTIBACTERIAL PROPERTIES OF MEDICINAL PLANTS SAUROPUS ANDROGYNUS L. AND ERYTHRINA VARIEGATA L. - Kb, Laveena; M, Chandra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim of the present study was to evaluate the bioactive, antioxidant, and antibacterial activity of methanolic extracts of medicinal plants Erythrina variegata L., and Sauropus androgynus L. Methods: Total phenolic, flavonoid, tannin content, total antioxidant capacity, 1, 1diphenyl-2-picryl hydrazyl radical scavenging activity, and reducing power assay of the extracts were determined by spectrophotometric methods. Results: Total phenolic, flavonoid, and tannin content was more in E. variegata compared to S. androgynus, and the alkaloid, saponin, and carotenoid content was high in S. androgynus. The overall antioxidant activity of S. androgynus was found to be higher than E. variegata. Antibacterial activities of the selected plants were studied against human pathogenic organisms, namely Escherichia coli and Staphylococcus aureus. Conclusions: The present study reveals that the selected plants would exert several beneficial effects by virtue of their natural antioxidant activity; further characterization of the phenolic composition is needed and could be harnessed as drug formulation.